Efficient Transformer Architectures for Diabetic Retinopathy Classification from Fundus Images: DR-MobileViT, DR-EfficientFormer, and DR-SwinTiny - Saadna, Yassmina; Mezzoudj, Saliha; Khelifa, Meriem (Informatica, 2025)
Diabetic retinopathy (DR) is a prevalent cause of vision loss, necessitating efficient diagnostic tools, particularly in resource-limited settings. This study presents three lightweight transformer-based models— DR-MobileViT, DR-EfficientFormer, and DR-SwinTiny—for automated DR classification from fundus images (APTOS 2019: 3,662 images; Messidor-2: 1,748 images). After preprocessing including resizing to 224×224 pixels and CLAHE enhancement, these models, leveraging compact architectures (1.8–3.5M parameters), are trained using an AdamW optimizer with data augmentation. DR-MobileViT integrates convolutional and transformer layers, DR-EfficientFormer employs a dimension-consistent design, and DRSwinTiny utilizes shifted window attention. All models were initialized with ImageNet pretrained weights. Evaluated on the APTOS 2019 and Messidor-2 datasets, they achieve quadratic weighted kappa (QWK) scores up to 0.89 and areas under the ROC curve (AUC) up to 0.95. These models approach the performance of top-performing CNN ensembles from the APTOS 2019 challenge (which exceed 40M parameters) while reducing inference times to 10–15 ms/image (NVIDIA P100 GPU) and computational overhead by over 90%. These results indicate their potential for scalable, point-of-care DR screening, offering a viable solution for early detection in underserved regions.